MyD88 orchestrates fatty acid metabolism in tumor-associated macrophages and non-alcoholic fatty liver disease-related hepatocarcinogenesis - Chen, Haiqiang; Yan, Xuanxuan; Li, Zuyin; Deng, Zhenzhong; Gu, Jianchun; Zeng, Fanxin; Li, Zhao; Zhang, Jinhua (Frontiers in Immunology, 2025)
IntroductionNon-alcoholic fatty liver disease (NAFLD) is a growing cause of cirrhosis and hepatocellular carcinoma (HCC). Toll-like receptors (TLRs) and their adapter protein, myeloid differentiation factor 88 (MyD88), are activated in NAFLD and contribute to its development. However, the specific role of MyD88 in myeloid cells that regulate NAFLD-associated hepatocarcinogenesis remains unknown.MethodsWe used a diethylnitrosamine/high-fat diet-induced HCC mouse model with selective deletion of MyD88 from myeloid cells to investigate NAFLD-HCC, and we evaluated the development of NAFLD-HCC histologically and genetically.ResultsMyeloid cell MyD88-deficient (LyzMyD88−/−) mice were protected from diet-induced obesity and developed fewer and smaller liver tumors. MyD88 deficiency in myeloid cells also attenuated macrophage M2 polarization and fat accumulation in HCC tissues. Mechanistically, the loss of MyD88 signaling specifically inhibited macrophage M2 polarization, with decreased metabolism in a SREBP1/STAT6 pathway-dependent manner. Furthermore, liver tumor growth was attenuated in mice treated with a SREBP1 inhibitor. High SREBP1 and CD163 expression in HCC was associated with shorter survival of patients with HCC. Thus, our results indicate that MyD88 in myeloid cells promotes NAFLD-related HCC progression and may be a promising therapeutic target for HCC treatment.DiscussionMyD88 in macrophages has a promotional role in NAFLD-associated HCC. MyD88 promotes macrophage M2 polarization, which enhances the progression of NAFLD to HCC by activating the SREBP1/STAT6 pathway. MyD88 in macrophages may be a potential therapeutic and/or preventive target for NAFLD-associated HCC.